Use of Dichotomous Choice Contingent Valuation Method to Value the Manukan Island, Sabah - Alias, Radam; Shazali, Abu Mansor (Universiti Putra Malaysia Press, 2005)
This study presents the application of dichotomous choice contingent valuation method (CVM) to value outdooors-recreational resources in Manukan Island, Sabah. Both the logit and probit models are used to analyse the primary data obtained through personal interview. The maximum likelihood estimates of this model show that income and proce are significant variables in determining one is willingness to pay (WTP). The WTP figure derived from the model shows that it is much higher than present fees charged to the the visitors. This study has also estimates the revenue that could be derived is the fees were charged according to the WTP framework.